2018
DOI: 10.1111/cge.13227
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of KCTD3‐related developmental epileptic encephalopathy

Abstract: The association between KCTD3 gene and neurogenetic disorders has only been published recently. In this report, we describe the clinical phenotype associated with 2 pathogenic variants in KCTD3 gene. Seven individuals (including one set of monozygotic twin) from 4 consanguineous families presented with developmental epileptic encephalopathy, global developmental delay, central hypotonia, progressive peripheral hypertonia, and variable dysmorphic facial features. Posterior fossa abnormalities (ranging from Dand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…While KCTD3 has been associated with neurogenetic and neurodevelopmental disorders [ 1 , 91 ], no correlation with cancer has been reported so far.…”
Section: Group Dmentioning
confidence: 99%
“…While KCTD3 has been associated with neurogenetic and neurodevelopmental disorders [ 1 , 91 ], no correlation with cancer has been reported so far.…”
Section: Group Dmentioning
confidence: 99%
“…Homozygous KCTD3 mutations were identified in three additional families, one harboring the same frameshift mutation (c.1036_1073del, p.P346Tfs*4), and the other two harboring a missense mutation (c.166C > T, p.Arg56*) . KCTD3 patients exhibit global developmental delay, seizures, and cerebellar hypoplasia …”
Section: Kctd Genes Associated With Neurodevelopmental and Neuropsychmentioning
confidence: 99%
“…90 KCTD3 patients exhibit global developmental delay, seizures, and cerebellar hypoplasia. 88,90 The biological function of KCTD3 protein has not been investigated in-depth, but one study provides some evidence that links KCTD3 with the nervous system. Mouse Kctd3 was identified as a binding partner of Hcn3 (hyperpolarization-activated cyclic nucleotide-gated channel) in a yeast two-hybrid screen.…”
Section: Kctd3 In Neurocognitive Diseasementioning
confidence: 99%
“…Kctd3 and Hcn3 co-localize in the cerebellum, hypothalamus, and midbrain and Kctd3 upregulates the expression of Hcn3 (Cao-Ehlker et al, 2013). HCN3 modulates synaptic strength and cellular excitability (Biel et al, 2009;Huang et al, 2011). Faqeih et al (2018 reported seven cases with severe GDD, epilepsy, and cerebellar hypoplasia, of which five were carrying P346Tfs * 4 and the other two were carrying R56 * mutations.…”
Section: Kctd3mentioning
confidence: 99%